Aortic-Valve Stenosis — From Patients at Risk to Severe Valve Obstruction - Otto, Catherine M; Prendergast, Bernard (The New England journal of medicine, 2014)
Aortic-valve stenosis is a progressive condition; end-stage disease leads to death due to obstruction of left ventricular outflow. Aortic-valve replacement is the only effective therapy. Transcatheter aortic-valve replacement is appropriate in patients at very high surgical risk. Valvular aortic stenosis is a progressive disease in which the end stage is characterized by obstruction of left ventricular outflow, resulting in inadequate cardiac output, decreased exercise capacity, heart failure, and death from cardiovascular causes. The prevalence of aortic stenosis is only about 0.2% among adults between the ages of 50 and 59 years but increases to 9.8% in octogenarians, with an overall prevalence of 2.8% in adults older than 75 years of age. 1 , 2 Although mortality is not increased when aortic stenosis is asymptomatic, the rate of death is more than 50% at 2 years for patients with symptomatic . . .